Impact assessment of Adolescent development program in the selective border regions of Bangladesh (BRAC Research and Evaluation Division, 2022)
Border Adolescent Development Program (ADP) was implemented in the border areas of Bangladesh. The main objective of this program was to make the adolescents, their parents, and the communities aware of the social and legal issues like HIV/AIDS, gender equality, marriage and dowry. The objective of this study was to assess the impact of Border ADP. We used two rounds of survey data on the same adolescents collected in 2008 (baseline) and 2010 (follow-up). In analyzing the data, we used the difference-in-difference technique. We found a positive impact of the program on overall awareness among adolescents and their parents as well as capacity development of adolescents through life skill training. On the other hand, on many issues like the legal age of marriage and subsequent marriage the level of awareness of the adolescents and their parents still remains low. We suggested that ADP should arrange a fixed place where the adolescents can spend their time playing and reading, and hang there different awareness creating posters and leaflets/brochures. The program can also provide more leaflets/brochures or posters to the adolescents to display those in their houses and other places for enhancing awareness among all walks of people in general.